Kekerabatan Bahasa Sasak dan Bahasa Mbojo - Irmansyah, Sera Seftiana Putri; Hendrokumoro, Hendrokumoro (Jurnal Pendidikan Bahasa dan Sastra, 2023)
Comparative historical linguistic analysis is an approach in knowing the kinship relationship between one language and another. This study aims to determine the kinship between Sasak and Mbojo languages, by making a comparison between Sasak and Mbojo languages based on 200 Swadesh words. there were four informants used in this study to obtain the data, two speakers of Sasak and Mbojo languages respectively. The research instrument was the researcher herself assisted by a work analysis table listing 200 Swadesh vocabularies. This research is a qualitative-quantitative study using interview techniques in the process of obtaining the data. The results were then analyzed using the Lexicostatistical method, after which they were described. The results of this study indicate that Sasak language and Mbojo language are not only geographically close together, but the two languages are also related to one another with a kinship percentage of 19%. This is evidenced by the similarity of vocabulary in both languages. The Sasak and Mbojo languages are thought to have been a single language in 4256 – 3622 AD. Then the two languages, namely Sasak and Mbojo began to separate from their proton language between 2233 – 1599 AD (calculated in 2023). In Sasak and Mbojo languages, several phonemic correspondences are also found, namely /b/ ~ /w/, /t/ ~ /d/, /ʔ/ ~ /ø/, and /s/ ~ /ø/.